A rare case of acute type A aortic dissection in a patient with systemic lupus erythematosus (Rheumatology Reports, 2011)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease. The vascular lesions in SLE usually represent small vessel vasculitis. The number of reports of vascular conditions in patients with SLE has increased possibly due to the availability of better imaging modalities and increased patient survival secondary to the use of immunosuppressive agents. However, only a limited number of cases of aortic dissection have been published in the English literature.